PEMBAJAKAN KAPAL DI LAUT LEPAS DITINJAU DARI HUKUM INTERNASIONAL (STUDI KASUS KAPAL MV JAHAN MONI) - Yudi Tri Anantha; Arif Arif; Deni Purba (Journal of USU International Law, 2013)
ABSTRACT Piracy on the high seas either conducted by foreign vessels, as well as by domestic vessels in international waters lately been causing anxiety for international shipping. Repression high seas piracy is a crime, based on the force of international law relating to the high seas piracy. A ship M.V. Jahan Moni Bangladesh flagged off the Indian coast in the Arabian Sea was hijacked by the Somali people. The Somali piracy began to board the ship after chasing MV Jahan Moni in the Arabian Sea. Problems posed in this study is how the arrangement piracy on the high seas under international law, how the hijacking of the MV Jahan Moni and how efforts in addressing the problem of piracy on the high seas in cases of MV Jahan Moni? The method of research conducted with normative legal research or legal research library is done by researching the literature, and empirical legal research. Research the applicable law is normative or legal research is also called study of literature (library research) with the acquisition of secondary data sourced cider magazines, books, journals, newspapers, online websites, and other library documents. Based on the explanations that have been described in previous chapters, it can be concluded following a piracy action on the high seas and in general initially were motivated by economic factors. But in its development and in the present situation, the phenomenon of piracy in the context of acts of violence on the high seas wider. This is considering the possibility of the threat of terrorism in the background of both the Strait of non-economic issues (ideological), where it is possible that these actions are also carried out on the high seas, as well as ships at sea. Setting piracy on the high seas under international law that is based on the 1982 UN Convention on the Law of the Sea. Geneva Convention is also in line with Article 105 of UNCLOS which states in the high seas, or in every other place outside the jurisdiction of any State every State may seize a ship or aircraft piracy or a ship or aircraft taken by piracy and under the control of piracy and arrest the people who seized the goods on board. Changes or reconsideration (revision) can be done by expanding international jurisdictions with additional protocol, adding protocol in the United Nations Convention On The Law of the Sea (UNCLOS 1982) regarding the mechanisms to prosecute pirates, UNCLOS in 1982 through amendments to the provisions of article 311 adds piracy in Sea as one of the offenses that can be prosecuted in the International Criminal Court or the International Criminal Court (ICC) and establish special courts that deal with piracy at sea. Keywords: Ship Piracy on the high seas